(untitled) (Environment & Health, 2019)
Background: Nowadays, breast cancer is the most common hormone-dependent cancer among women worldwide. Etiology of breast cancer is multifactorial. The environmental endocrine disrupting chemicals (EDCs), including persistent organochlorine pollutants, are one of supposed factors for the increase of the incidence of breast cancer. Objective: We analyzed the literary data concerning the role of some persistent organochlorine chemicals such as DDT, dioxins and polychlorinated biphenyls in breast cancer formation. Results: The analysis of the epidemiological studies, despite their small number, demonstrates clearly the relationship of the exposure of studied endocrine disruptors with an increased risk of breast cancer in women. It has been established that exposure of EDCs during critical time periods (in utero, neonatal and pubertal), when hormones affect cell differentiation and tissue development, can disrupt the development of breast tissues and lead to the appearance of breast cancer in adult women. The results of the analysis confirm the relevance of the problem and the need in further research and solution of the issues of the population’s protection from the harmful effects of endocrine disruptors.